The Implementation Of Think-Pair-Share Technique To Improve Students’ Speaking Ability - Revira Widiya Putri; Dangin (LPPM Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The aim of this research was to find out the improvement of students' speaking ability through Think-Pair-Share technique. This research was carried out using Classroom Action Research. This research involved 32 students of class VIII A of SMP Al-Ma’arif Bantul in the academic year of 2022/2023 and the English teacher as the research collaborator. The research were qualitative and quantitative data. Qualitative data were obtained by observing the teaching and learning process and interviewing the teacher and students at SMP Al-Ma’arif Bantul. While quantitative data were acquired conducting through pre-test, progress test (cycle 1), and post-test (cycle 2). The research procedure consists of planning, acting, observing, reflection. According to the findings of this study, there has been a significant improvement in the students' speaking ability since the Think-Pair-Share technique was implemented in the teaching and learning process. The results of the students' speaking scores backed up these findings. The mean improved from 69.5 in Cycle 1 to 78 in Cycle 2. It indicated that they improved significantly in some aspects of their speaking skills, such as pronunciation, intonation and stress, comprehension, grammar, and vocabulary. Aside from improving their speaking score, the Think-Pair-Share technique encouraged students to gain confidence and become excited to speak up in front of the class.